GUIDED IMAGERY WITH DIGITAL THERAPY VIRTUAL REALITY AS PAIN SCORE AMONG BREAST CANCER PATIENTS: A RANDOMIZED CONTROLLED TRIAL - Primayanthi, Anak Agung Ayu Emi; Gayatri, Dewi; Abd Rahman, La Ode; Nuraini, Tuti; Waluyo, Agung (Universitas Aisyah Pringsewu, 2024)
Breast cancer is the most common cancer worldwide. Breast cancer has the highest rate around 42.1 per 100,000 in Indonesian. The most common problems experienced are physical problems such as pain. Pain is related to the patient's quality of life. Digital-based guided imagery with virtual reality in pain management are still rarely used. This study aims to determine the effectiveness of guided imagery using digital therapy virtual reality in breast cancer patients. The method uses RCT with a parallel design. 60 respondents who were randomized using block randomization into 30 in both control and intervention groups. Conducted at Dharmais Cancer Hospital using virtual reality for 10-15 minutes in intervention group and digital leaflets to control group. Measurements using the NRS were carried out every day for 7 days. The results showed that guided imagery with virtual reality was able to reduce the pain scale in breast cancer patients compared to the control group with P = 0.000 (? 0.05). The use of virtual reality can be used as a reference for oncology nurses in providing non-pharmacological therapy to reduce pain and stress in patients especially breast cancer patients.